Perancangan Aplikasi Sistem Penjualan pada LCB Cake & Beyond Menggunakan Metode Waterfall - Sandy, Fredy Kurnia; Sukanta, Sukanta (Universitas Indraprasta PGRI Jakarta, 2025)
In the ever-growing business world, effective and efficient data management is the key to success. Along with the need for automation and better data management, the implementation of database systems is a relevant solution. Database systems allow the storage, processing, and presentation of information in a structured and accurate manner, thus helping to improve operational efficiency and data accuracy. One of the challenges faced by many businesses, including LCB Cake & Beyond, is that the transaction process is still done manually. Conventional data recording is not only time-consuming, but also has a high risk of recording errors that can hinder operations and decision-making. Therefore, this research aims to design and implement a database application system to optimize the ordering process and store data management. The method used is waterfall with the help of Microsoft Access software. This system is designed to automate the process of data input, sales recording, and report generation quickly and accurately. The results showed that the database application developed was able to improve operational efficiency and minimize errors in the data management process, as well as provide convenience for users in accessing real-time information.